2021
DOI: 10.1038/s41698-021-00209-9
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian multi-source regression and monocyte-associated gene expression predict BCL-2 inhibitor resistance in acute myeloid leukemia

Abstract: The FDA recently approved eight targeted therapies for acute myeloid leukemia (AML), including the BCL-2 inhibitor venetoclax. Maximizing efficacy of these treatments requires refining patient selection. To this end, we analyzed two recent AML studies profiling the gene expression and ex vivo drug response of primary patient samples. We find that ex vivo samples often exhibit a general sensitivity to (any) drug exposure, independent of drug target. We observe that this “general response across drugs” (GRD) is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 73 publications
(73 reference statements)
1
16
0
Order By: Relevance
“…We and others have observed that drug response patterns in AML are sometimes correlated with maturation state of AML tumor cells, with certain drugs exhibiting stronger efficacy against tumors with less differentiated cell state (e.g., BCL2i, cyclin dependent kinase 4/6 [CDK4/6]i; Kuusanmaki et al, 2020;Majumder et al, 2020;Pei et al, 2020;Romine et al, 2021;Zhang et al, 2020) and others showing better efficacy against tumors with more differentiated state (e.g., bromodomain containing 4 [BRD4/BET] i, mitogen-activated protein kinase kinase [MAPKK/MEK]i; Romine et al, 2021;White et al, 2021). Analytical approaches can facilitate the deconvolution of deep-sequencing data to infer proportions of distinct cell types (Avila Cobos et al, 2018), and single-cell sequencing technology has recently defined gene expression patterns for six distinct cell types in AML (hematopoietic stem cell [HSC]-like, progenitor-like, granulocyte-monocyte progenitor [GMP]-like, promonocyte-like, monocyte-like, and conventional dendritic cell [cDC]-like types; Van Galen et al, 2019).…”
Section: Deconvoluting Aml Cell Maturation Statementioning
confidence: 99%
“…We and others have observed that drug response patterns in AML are sometimes correlated with maturation state of AML tumor cells, with certain drugs exhibiting stronger efficacy against tumors with less differentiated cell state (e.g., BCL2i, cyclin dependent kinase 4/6 [CDK4/6]i; Kuusanmaki et al, 2020;Majumder et al, 2020;Pei et al, 2020;Romine et al, 2021;Zhang et al, 2020) and others showing better efficacy against tumors with more differentiated state (e.g., bromodomain containing 4 [BRD4/BET] i, mitogen-activated protein kinase kinase [MAPKK/MEK]i; Romine et al, 2021;White et al, 2021). Analytical approaches can facilitate the deconvolution of deep-sequencing data to infer proportions of distinct cell types (Avila Cobos et al, 2018), and single-cell sequencing technology has recently defined gene expression patterns for six distinct cell types in AML (hematopoietic stem cell [HSC]-like, progenitor-like, granulocyte-monocyte progenitor [GMP]-like, promonocyte-like, monocyte-like, and conventional dendritic cell [cDC]-like types; Van Galen et al, 2019).…”
Section: Deconvoluting Aml Cell Maturation Statementioning
confidence: 99%
“…(3) The BFL1/MCL1 signature was enriched in monocytic AMLs that have been reported to be resistant to BCL2 inhibition (Additional file 2 : Fig S17) [ 73 , 74 ]. This signature was also highly correlated with an existing monocyte signature correlated with BFL1 and MCL1 expression and venetoclax resistance (Additional file 2 : Fig S18) [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…They have been leaders in this movement; three years ago, in this journal, this team made the novel observation that venetoclax response might vary by the degree of maturation of AML, with more primitive disease having higher sensitivity and more mature forms having greater resistance (6). This unexpected observation of stage of differentiation as a predictive marker has since been validated, by our group and others, in retrospective studies of patients receiving treatment and with further mechanistic work (7,8).…”
mentioning
confidence: 90%